Georgia Architectural and Historic Properties Survey of Quitman [385] 603 W. Screven, Valdosta, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Quitman [385] 603 W. Screven, Valdosta, Ga. December 1980. Georgian plan - irregular floor plan. Hipped and gabled tin roof. Surrounding shed porch (screened). Shiplap siding. Palladian dormer. Sash windows with 2/2 lights. Interior chimneys. Good condition. Date of Construction: c. 1905 - 1910. Significant as part of a potential National Register historic district along Screven St. and including the commercial area.
1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.21 MB (1,275,319 bytes).
Keywords: Historic buildings; Lowndes County Historical Society (Lowndes County, Ga.); Real property surveys; Brooks County (Ga.); Quitman (Ga.)